Alzheimer’s Disease-Like Pathology Triggered by Porphyromonas gingivalis in Wild Type Rats Is Serotype Dependent - Díaz-Zúñiga, Jaime; More, Jamileth; Melgar-Rodríguez, Samanta; Jiménez-Unión, Matías; Villalobos-Orchard, Francisca; Muñoz-Manríquez, Constanza; Monasterio, Gustavo; Valdés, José Luis; Vernal, Rolando; Paula-Lima, Andrea (Frontiers in Immunology, 2020)
Periodontal disease is a disease of tooth-supporting tissues. It is a chronic disease with inflammatory nature and infectious etiology produced by a dysbiotic subgingival microbiota that colonizes the gingivodental sulcus. Among several periodontal bacteria, Porphyromonas gingivalis (P. gingivalis) highlights as a keystone pathogen. Previous reports have implied that chronic inflammatory response and measurable bone resorption are observed in young mice, even after a short period of periodontal infection with P. gingivalis, which has been considered as a suitable model of experimental periodontitis. Also, encapsulated P. gingivalis strains are more virulent than capsular-defective mutants, causing an increased immune response, augmented osteoclastic activity, and accrued alveolar bone resorption in these rodent experimental models of periodontitis. Recently, P. gingivalis has been associated with Alzheimer's disease (AD) pathogenesis, either by worsening brain pathology in AD-transgenic mice or by inducing memory impairment and age-dependent neuroinflammation middle-aged wild type animals. We hypothesized here that the more virulent encapsulated P. gingivalis strains could trigger the appearance of brain AD-markers, neuroinflammation, and cognitive decline even in young rats subjected to a short periodontal infection exposure, due to their higher capacity of activating brain inflammatory responses. To test this hypothesis, we periodontally inoculated four weeks-old male Sprague-Dawley rats with K1, K2, or K4 P. gingivalis serotypes and the K1-isogenic non-encapsulated mutant (GPA), used as a control. 45-days after periodontal inoculations with P. gingivalis serotypes, rat´s spatial memory was evaluated for six consecutive days in the Oasis maze task. Following functional testing, the animals were sacrificed, and various tissues were removed to analyze alveolar bone resorption, cytokine production, and detect AD-specific biomarkers. Strikingly, only K1 or K2 P. gingivalis-infected rats displayed memory deficits, increased alveolar bone resorption, pro-inflammatory cytokine production, changes in astrocytic morphology, increased Aβ1-42 levels, and tau hyperphosphorylation in the hippocampus. None of these effects were observed in rats infected with the non-encapsulated bacterial strains. Based on these results, we propose that the bacterial virulence factors constituted by capsular polysaccharides play a central role in activating innate immunity and inflammation in the AD-like pathology triggered by P. gingivalis in young rats subjected to an acute experimental infection episode.